Ethnopharmacological Uses, Phytochemistry, and Pharmacological Properties of Croton macrostachyus Hochst. Ex Delile: A Comprehensive Review. (12th October 2017) - Maroyi, Alfred
Abstract : Croton macrostachyus is widely used as herbal medicine by the indigenous people of tropical Africa. The potential of C. macrostachyus as herbal medicine, the phytochemistry, and pharmacological properties of its parts used as herbal medicines are reviewed. The extensive literature survey revealed that C. macrostachyus is traditionally used to treat or manage at least 81 human and animal diseases and ailments. The species is used as herbal medicine for diseases and ailments such as abdominal pains, cancer, gastrointestinal disorders, malaria, pneumonia, sexually transmitted infections, skin infections, typhoid, and wounds and as ethnoveterinary medicine. Multiple classes of phytochemicals such as alkaloids, amino acids, anthraquinones, carbohydrates, cardiac glycosides, coumarins, essential oil, fatty acids, flavonoids, phenolic compounds, phlobatannins, polyphenols, phytosteroides, saponins, sterols, tannins, terpenoids, unsaturated sterol, vitamin C, and withanoides have been isolated from the species. Pharmacological studies on C. macrostachyus indicate that it has a wide range of pharmacological activities such as anthelmintic, antibacterial, antimycobacterial, antidiarrhoeal, antifungal, anticonvulsant and sedative, antidiabetic, anti-inflammatory, antileishmanial, antioxidant, antiplasmodial, and larvicidal effects. Croton macrostachyus has potential as a possible source of a wide range of pharmaceutical products for the treatment of a wide range of both human and animal diseases and ailments.